Duality, Rigidity and Planar Parallax - Criminisi, Antonio; Reid, I.; Zisserman, A. (1998 European Conference on Computer Vision, 1998)
We investigate the geometry of two views of seven points, four of which are coplanar, and the geometry of three views of six points, four of which are coplanar. We prove that the two are dual, and that the fundamental geometric constraints in each case are encapsulated by a planar homology. The work unifies a number of previously diverse results related to planar parallax, duality and planar homologies.